Efektivitas Token Ekonomi Untuk Meningkatkan Perilaku Mengantri Pada Anak TK - Rafika Febrilla (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
This study aims to improve queuing behavior in early childhood by using token economy techniques. The short-term target of this study is that kindergarten children are able to apply queuing behavior in various activities at school, while the long-term target is that queuing behavior can be maintained and applied in various situations outside of school. This study used a quantitative approach with a quasi-experimental method, where the research participants were Kemala Bhayangkari II Bukittinggi kindergarten students aged 5-7 years. Data collection was carried out through observation using a checklist instrument based on Chairilsyah's (2015) theory. The research process consists of several stages, namely screening to determine the target behavior, taking a baseline for seven days to measure initial behavior, and providing interventions with token economy techniques. The tokens used were star-shaped stickers, which were given to students as reinforcers after they demonstrated appropriate queuing behavior. The data obtained were analyzed to evaluate the effectiveness of the token economy technique in improving queuing behavior. The results showed that the token economy technique is effective in improving queuing behavior in kindergarten children. In addition, this study also highlights the importance of providing consistent reinforcers to encourage sustainable behavior change. This technique can be adapted for various situations involving young children in learning social behaviors.